Distributional patterns of the Brazilian free-tailed bat Tadaridaâ€¯brasiliensis in the Peruvian territory - Zegarra, Orlando; Pacheco, Jaime; Pacheco, Víctor (THERYA, 2020)
The molossid bat Tadarida brasiliensis has a wide and apparently continuous distribution in South America. Although it has been reported in several localities of both versants of the Peruvian Andes, the potential distribution for this species has not been formally analyzed. Therefore, we describe its distributional pattern in the territory and provide comments about the possible influence of the Andes in its distribution. We gathered occurrence records from museums, acoustic surveys, literature, GBIF and Vertnet sources, and we selected localities to minimize spatial correlation. After defining a minimum-convex polygon of Peruvian records as background area, we use Maxent software with bioclimatic variables to construct species distribution models. Several models were evaluated using different metrics, and the model with the lowest AICc was selected. Then, the model was projected for Peruvian territory. Tadarida brasiliensis is reported for the first time in Cajamarca, Piura and Ica departments. The potential distribution model showed two disjunct suitable areas, one for the Pacific versant and other for the Amazonian versant of the Andes, but connected with moderate suitable conditions in the Huancabamba Depression region in northern Perú. Mean diurnal range and annual mean temperature were identified as the main limiting factors for the potential distribution of this species in this territory. Tadarida brasiliensis exhibits a discontinuous distribution in the Peruvian territory. In northern part, the Huancabamba depression zone has climatic conditions that may allow the east-west dispersal for this species. In central and southern parts, the higher crest of the Andes (> 4,500 m) has low suitable conditions due to the extreme climate. In the eastern, the lowland Amazonian forests has low suitability for this species, probably due to high temperatures. We suggest that the Andes could be acting a biogeographical barrier that limits the dispersal for this species, but population-genetic studies are needed to confirm this hypothesis. We identified that temperature is the main climatic factor that limit the dispersal of this bat. In conclusion, T. brasiliensis is mainly associated with desert and Andean slopes ecosystems in Perú, and we highlight the importance of incorporating acoustic records in the analysis of its distribution patterns.